Role of pro-inflammatory cytokines in Alzheimer's disease and neuroprotective effects of pegylated self-assembled nanoscaffolds - Varsha Rani; Rinki Verma; Krishan Kumar; Ruchi Chawla (Elsevier, 2023)
Neurodegeneration and synaptic loss in Alzheimer's disease (AD) lead to impairment in memory functions. Neuroinflammation causes activation of microglia and astrocytes cells that locally and systemically produces inflammatory cytokines which can serve as early diagnostic markers or therapeutic targets in AD. Pro-inflammatory cytokines (Interleukins (IL-1β, IL-6 and IL-10) and tumor necrosis factor (TNF α)) levels were estimated in serum, cerebral tissue, hepatic tissue, and renal tissue in treatment groups of scopolamine-induced amnesia mice model using ELISA protocol. The results showed that cerebral tissue of AD mice exhibited elevated levels of IL1β, IL6, IL10 and TNFα which indicate contribution of pro-inflammatory cytokines in the progression of AD. A significant reduction in the concentration of IL1β, IL-10 and TNF-α were noticed in serum, cerebral tissue and hepatic tissue of animal group treated with marketed memantine tablet (Admenta), pure memantine drug (MEMp), memantine-poly (lactic-co-glycolic acid) self-assembled nanoscaffolds (MEM-PLGA) SANs, Polyethylene Glycol coated memantine-poly (lactic-co-glycolic acid) self-assembled nanoscaffolds [(PEG-MEM-PLGA) SANs] and Polyethylene Glycol coated memantine-poly [(lactic-co-glycolic acid)] self-assembled nanoscaffolds grafted with Bone Marrow Derived Stem Cell ((PEG-MEM-PLGA) SANs-BMSc), whereas a high level of IL-6 was observed in hepatic tissue, cerebral tissue and renal tissues of normal and AD induced mice which showed the emerging potential of IL-6 cytokines that can trigger either neurons survival after injury or causing neurodegeneration and cell apoptosis. The Neuroregenerative potential of stem cells helps in the proliferation of neuronal cell and thus improves cognition in AD animal model.